Rightful Resistance in the Colombian conflict. A theoretical reflection based on a Peace Community - Naucke, Philipp; Halbmayer, Ernst (Revista de Antropología Social, 2016)
This article considers the opportunities of civilians to peacefully resist violent conflicts or civil wars. The argument developed here is based on a field-based research on the peace community San José de Apartadó in Colombia. The analytical and theoretical framework, which delimits the use of the term ‘resistance’ in this article, builds on the conceptual considerations of Hollander and Einwohner (2004) and on the theoretical concept of ‘rightful resistance’ developed by O’Brien (1996). Beginning with a conflict-analytical classification of the case study, we will describe the long-term socio-historical processes and the organizational experiences of the civilian population, which favoured the emergence of this resistance initiative. The analytical approach to the dimensions and aims of the resistance of this peace community leads to the differentiation of O`Brian’s concept of ‘rightful resistance’.
Keywords: Resistance; Civilian Population; Armed Conflict; Peace Community.